К фауне нематод некоторых злаковых и бобовых растений Стрелецкой степи - Сигарева, Д.Д. (Вестник зоологии, 1968)
Three type of plants feather grass, clover and alfalfa—were examined for their in-fection with nematodas in Streletskaya steppe (Kursk region, the branch of the Central-chernozem State Reservation). 60 species of nematoda are found out, belonging to 2 sub-classes, 4 orders, 14 families and 26 genera. A list of found phytonematodas is presented. The diversity of the species composition and a great number of nematodas can be explained by the conditions favourable for their development in reservation: high temperatures in summer, a sufficient quantity of moisture, thick and various (as to the species composition) vegetation and uncultivated soil.